PENINGKATAN PENGELOLAAN PERPUSTAKAAN SEKOLAH MELALUI SUPERVISI MANAJERIAL DI SEKOLAH BINAAN KABUPATEN MEMPAWAH - Suherni, Erni (Jurnal Pembelajaran Prospektif, 2021)
School management realizes that in the interests of developing the quality of students, apart from receiving face-to-face learning and activities related to library / field testing, of course, a lot of compulsory and companion reading materials are needed. But in reality, students are only provided with a number of books that have been packaged according to the curriculum for each lesson. Thiscondition makes the school library does not have a clear program. This existence is understandable, because indeed in every school accreditation, the library is not designed to support the main needs. The function of the school library is essentially to provide information services for users of library services in schools. Information services are provided to support the smooth implementation oflearning activities. Through managerial supervision, it will improve the management of materials processing, services, and library program planning. In addition, a comparative study to other schools will be one solution to provide examples of library management standards.